CareTrack Aged: the appropriateness of care delivered to Australians living in residential aged care facilities: a study protocol. Issue 6 (25th June 2019) - Hibbert, Peter D; Wiles, Louise K; Cameron, Ian D; Kitson, Alison; Reed, Richard L; Georgiou, Andrew; Gray, Len; Westbrook, Johanna; Augustsson, Hanna; Molloy, Charlotte J; Arnolda, Gaston; Ting, Hsuen P; et al.
Abstract : Introduction: The aged population is increasing rapidly across the world and this is expected to continue. People living in residential aged care facilities (RACFs) represent amongst the sickest and frailest cohort of the aged population, with a high prevalence of chronic conditions and complex comorbidities. Given the vulnerability of RACF residents and the demands on the system, there is a need to determine the extent that care is delivered in line with best practice ('appropriate care') in RACFs. There is also a recognition that systems should provide care that optimises quality of life (QoL), which includes support for physical and psychological well-being, independence, social relationships, personal beliefs and a caring external environment. The aims of CareTrack Aged are to develop sets of indicators for appropriate care and processes of care for commonly managed conditions, and then assess the appropriateness of care delivered and QoL of residents in RACFs in Australia. Methods and analysis: We will extract recommendations from clinical practice guidelines and, using expert review, convert these into sets of indicators for 15 common conditions and processes of care for people living in RACFs. We will recruit RACFs in three Australian states, and residents within these RACFs, using a stratified multistage sampling method. Experienced nurses, trained in the CareTrack Aged methods ('surveyors'), will review care records of recruited residents within a 1-month period in 2019 and 2020, and assess the care documented against the indicators of appropriate care. Surveyors will concurrently assess residents' QoL using validated questionnaires. Ethics and dissemination: The study has been reviewed and approved by the Human Research Ethics Committee of Macquarie University (5201800386). The research findings will be published in international and national journals and disseminated through conferences and presentations to interested stakeholder groups, including consumers, national agencies, healthcare professionals, policymakers and researchers.